International intervention in the Balkans since 1995 - Siani-Davies, Peter (London ; New York : Routledge, 2003)
"This volume offers an analysis of the activities of the international community in the Balkans since the 1995 Dayton Agreement. There has been substantial investment in the region but so far the gains have been limited and doubts remain as to the extent that sustainable security has been enhanced. There is a need for serious reassessment of policies and priorities, but this depends on a careful analysis of past successes and failures. The contributors seek to provide this by examining intervention, not just in terms of military action and the activities of major international agencies at state level, but also the activities of outside NGOs within the local environment."--Provided by publisher.
This volume offers an analysis of the activities of the international community in the Balkans since the 1995 Dayton Agreement.
1. Intervention in the Balkans : an unfinished learning process / Mary Kaldor -- 2. The concept of humanitarian intervention / Vesselin Popovski -- 3. The controversies of Euro-Atlantic interventionism in the Balkans / Miroslav Hadz̆ić -- 4. Mostar : international intervention in a divided Bosnian town, 1994-2001 / Sumantra Bose -- 5. When our men arrive : UNMIK's post-conflict administration of Kosovo / Emmanuela C. Del Re -- 6. International intervention in Macedonia : from preventive engagement to peace implementation / Alice Ackermann -- 7. The impact of international intervention on domestic political outcomes : Western coercive policies and the Milošević regime / Jasna Dragović-soso -- 8. From kanun to capacity-building : the 'internationals', civil society development and security in the Balkans / Steven Sampson -- 9. Securing the community? An examination of international psychosocial intervention / Vanessa Pupavac -- 10. Beyond intervention? The Balkans, the Stability Pact and the European Union / David Phinnemore and Peter Siani-Davies -- 11. Gaps of concern : an inconclusive conclusion / Stephanie Schwandner-Sievers.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (Taylor & Francis, viewed on February 4, 2025).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: North Atlantic Treaty Organization -- Armed Forces -- Yugoslavia; Organisation du traité de l'Atlantique Nord -- Forces armées -- Yougoslavie; North Atlantic Treaty Organization; Operation Allied Force, 1999.; National security -- Balkan Peninsula; Yugoslavia -- History -- 1992-2003.; Balkan Peninsula -- History -- 20th century; Opération Force alliée, 1999.; Yougoslavie -- Histoire -- 1992-2003.; Balkans -- Histoire -- 20e siècle.; HISTORY -- General; Armed Forces; National security; Balkan Peninsula; Yugoslavia; Buitenlandse interventie; Internationale betrekkingen; 1900-2003; Electronic books; History